PENGARUH COUNTRY OF ORIGIN DAN BRAND IMAGE TERHADAP INTENTION BEHAVIOR MELALUI WORD OF MOUTH SEBAGAI VARIABEL INTERVENING (STUDI PADA MAHASISWA S1 PENGGUNA SMARTPHONE SAMSUNG DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO) - Amelinda, Talitha; Farida, Naili (Jurnal Ilmu Administrasi Bisnis, 2017)
This research is based on the growth of international and multinational markets which is potential to make the growth of foreign products entering Indonesia, especially in electronic gadgets such as a smartphone in particular. This phenomenon characterized by increasing number of users smartphone in the world from years 2013-2018. Smartphone samsung is currently a market leader in indonesia, but from years 2012-2015 the number of Samsung smartphone product sales in Semarang has decreased each year.The purpose of this research is to know the influence of country of origin and brand image against intention behavior through word of mouth as an intervening variable. This research type is explanatory research, with the techniques of datacollection through the questionnaire. Sampling techniques using a purposive sampling technique. The sample in this research are 100 respondents which is a Samsung smartphone use.This research using techniques of quantitative analysis. Quantitative analysis using the test validity, reliability tests, coefficient of correlation, simple regression analysis,the determination coefficient, significance tests (two directions), and analysis of sobel.The results of the research indicate that there is a positive influence of the variable country of origin and brand image against variables intention behavior and variable word of mouth. Based on the results of the analysis of sobel, known that there is a positive influence of the variable country of origin against intention behavior through word of mouth and there was also a positive influence on brand image against the intention of the variable behavior through word of mouth. Then the variable word of mouth can be said to be a partial mediation variables.